Inflation persistence and optimal monetary policy in the euro area - Pierpaolo Benigno; David López-Salido (European Central Bank (ECB), 2002)
In this paper we present supporting evidence of the existence of heterogeneity in inflation dynamics across euro area countries. Based on the estimation of New Phillips Curves for five major countries of the euro area, we find that there is significant inertial (backward looking) behavior in inflation in four of them, while inflation in Germany has a dominat forward looking component. We then present an optimizing agent model for the area emphasizing the hetergeneity in inflation persistence across regions. Allowing for such a backward looking component will affect the evaluation of the degree of nominal rigidities relevant for the monetary policy design. We explore the welfare implications of this circumstance by comparing the adjustment of the economies and the area as a whole in response to terms-of-trade shocks under four monetary policy rules: fully optimal, optimal inflation targeting, HICP targeting and output gap stabilization.
Keywords: E52; E58; 330; currency areas; Inflation Dynamics; optimal monetary policy